The impacts of transaction costs and peer effects on pig farmers’ willingness to participate in a pig manure outsourcing treatment project - Zhou, Kun; Wang, Huan; Zhang, Zhenwang; Li, Jianqiang (Frontiers in Sustainable Food Systems, 2024)
This study aimed to explore the key factors affecting pig farmers' willingness to participate in a pig manure outsourcing treatment project (PMOTP) from the perspectives of transaction costs and peer effects. Survey data from 512 pig farmers and the probit and Heckman probit models were used to estimate the impact of transaction costs and peer effects on farmers’ participation in the PMOTP. The results demonstrate that more than 52% of farmers are willing to participate in the PMOTP, and the average willingness to pay reaches 7.2 yuan/ton. Farmers' willingness to participate in the PMOTP decreases with asset specificity, transaction frequency and uncertainty but increases with peer effects. Moreover, peer effects attenuate the inhibitory effect of transaction costs on farmers' participation in the PMOTP. Heterogeneity analysis showed that large-scale farmers without the self-breeding and self-rearing model are more affected by transaction costs and peer effects than other farmers. Moreover, asset specificity and peer effects are likely to increase farmers' willingness to pay for the project, which suggests that larger farms are more willing to invest in the PMOTP. These findings provide a useful reference for establishing a model for sustainable environmental service projects in the farming industry.